REDESIGN MUSEUM SRI BADUGA - Rahy Rachmawan Sukardi (Jurnal Scientia, 2022)
West Java State Museum "Sri Baduga" is one of the many public museums in Indonesia under the auspices of the Ministry of Tourism and Culture. The West Java State Museum not only functions as a place for preserving objects that have scientific and cultural values, but also functions as a center for information on history, nature and culture as well as a place for cultural recreation about the province of West Java. Based on the classification in the guidelines for Standardizing Public Museums at the Provincial Level, the West Java State Museum "Sri Baduga" needs to have good infrastructure and is located in the right location, to support the three functions of the museum, namely a place for preserving information centers and places for cultural recreation related to history, nature and culture of the province of West Java. Bandung as the planning location is the capital of the province of West Java, which according to the policy of the Diparda of West Java will be made a tourist city with a development direction towards shopping tourism, arts and culture and entertainment. This is due to the lack of natural attractions in the city of Bandung. The reason for redesigning the Sri Baduga Museum is because the museum is currently considered less desirable and also requires additional site and additional space functions, which are expected to increase the interest of more visitors in the future